2012
DOI: 10.1002/pc.22335
|View full text |Cite
|
Sign up to set email alerts
|

Single‐wall carbon nanotubes dispersion behavior and its effects on the morphological and mechanical properties of the electrospun nanofibers

Abstract: The dispersion behavior of single‐walled carbon nanotube (SWCNT) has important effects on morphological and mechanical properties of SWCNT composite nanofibers. The relationship of the dispersion conditions with morphological and mechanical characteristics for SWCNT / polyacrylonitrile (PAN) / polyvinylpyrrolidone (PVP) composite nanofibers have been examined. The SEM and TEM analyses of the nanofibers revealed that the deformation in the nanofiber structures increases with increasing concentration of SWCNTs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…Many researchers have shown that PVP can improve the dispersion of CNTs through helical wrapping way [19,20]. It has been already proved that PVP also improves the dispersion of CNTs in polymer matrix, leading to the improvement of mechanical properties as compared with the nanocomposites containing untreated CNTs [21].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that PVP can improve the dispersion of CNTs through helical wrapping way [19,20]. It has been already proved that PVP also improves the dispersion of CNTs in polymer matrix, leading to the improvement of mechanical properties as compared with the nanocomposites containing untreated CNTs [21].…”
Section: Introductionmentioning
confidence: 99%
“…1d). However, considerable aggregation and local irregu larities in nanofibers structure by incorporating low concentrations of MWCNT (1-2 wt %) have been also reported by other researchers [22,23].…”
Section: Introductionmentioning
confidence: 62%
“…As described in the litera ture [19], mostly with decreasing the viscosity and increasing the conductivity of the electrospinning (Table 2). These variations can be related to the polymer chain conformation changes in the solution produced due to adding PANi CSA.…”
Section: Introductionmentioning
confidence: 98%
“…Such conduct ing electrospun nanofibers webs could be useful in The prepared solutions were added to a glass syringe with a needle tip (22G, L = 34 mm and D = 0.7 mm). The feeding rate of the polymer solutions was 0.25 mL/h and electrospinning voltage of 16 kV was applied to the needle, while the distance between the needle tip and the drum collector was chosen at 18 cm and the take up speed was set on 100 RPM [17,18]. The electrospinning of solutions were performed at 22 ± 5°C and constant relative humidity (30-35%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation